Process and results of the development of an ICNP® Catalogue for Cancer Pain - Marisaulina Wanderley Abrantes de Carvalho; Maria Miriam Lima da Nobrega; Telma Ribeiro Garcia (SciELO, 2013)
This was a methodological study conducted to describe the process and results of the development of an International Classification for Nursing Practice (ICNP®) Catalogue for Cancer Pain. According to the International Council of Nurses (ICN), this catalogue contains a subset of nursing diagnoses, outcomes, and interventions to document the implementation of the nursing process in cancer patients. This catalogue was developed in several steps according to the guidelines recommended by the ICN. As a result, 68 statements on nursing diagnoses/outcomes were obtained, which were classified according to the theoretical model for nursing care related to cancer pain into physical (28), psychological (29), and sociocultural and spiritual (11) aspects. A total of 116 corresponding nursing interventions were obtained. The proposed ICNP® Catalogue for Cancer Pain aims to provide safe and systematic orientation to nurses who work in this field, thus improving the quality of patient care and facilitating the performance of the nursing process.